Gambaran Perilaku Caring Perawat pada Pasien Pre Operasi di Ruang Rawat Inap Bedah Rumah Sakit Palembang - Utama, Yofa Anggriani (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Anxiety is a response given by an individual to a threat. The situation of a person who is waiting for an operation schedule shows an event that is full of uncertainty, it can cause fear and anxiety, it is necessary for nurses to apply caring behavior which is the focus of nursing practice. This study aims to determine the description of nurses' caring behavior for pre-operative patients in the surgical inpatient room at a hospital in Palembang. The research design used in this research is descriptive. The data collection technique was purposive sampling with a total of 79 respondents. From the research results, it was found that more nurses had positive caring behavior, namely 70 respondents stated that nurses' caring behavior was positive with a percentage of 88.6% and 9 respondents stated that nurses' caring behavior was negative with a percentage of 11.4%. The conclusion is that more nurses have positive caring behavior for preoperative patients in the Palembang Hospital Surgical Inpatient Room.